Discharge Planning Oleh Perawat terhadap Tingkat Kepuasan Pasien - Rahmadani, Nurul Reski; Tutik Agustini; Al Ihksan Agus; Rahmat Hidayat (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Discharge Planning is a continuous nursing process since the patient is hospitalized until after returning from the hospital, which aims to reduce the recurrence rate and the occurrence of disease complications while at home to increase patient satisfaction. This study aimed to determine the effect of discharge planning on the level of patient satisfaction in the Baji Dakka Treatment Room at Labuang Baji Hospital. This research design uses quantitative research with a cross-sectional design approach. The sampling technique used purposive sampling with as many as 64 respondents in the Baji Dakka Treatment Room. The data analysis used in this study is the statistical analysis of the T-test. The results showed that there was an effect of discharge planning on the level of patient satisfaction with the Partial Test (T-test) with a T value of 2.075 > 1,669 and the results of p = 0.042 < 0.05 in the Room Treatment of Dakka Baji at Labuang Baji Hospital. This study concludes that there is an effect of discharge planning on the level of patient satisfaction in the Baji Dakka Treatment Room at Labuang Baji Hospital, with a p-value of 0.042 <0.05. Therefore, it is hoped that the implementation of the existing discharge planning will be maintained improved and given to all patients starting from the time the patient enters the treatment room until the day of discharge to increase patient satisfaction.